In vivo Host-Pathogen Interaction as Revealed by Global Proteomic Profiling of Zebrafish Larvae - Díaz-Pascual, Francisco; Ortíz-Severín, Javiera; Varas, Macarena A.; Allende, Miguel L.; Chávez, Francisco P. (Frontiers in Cellular and Infection Microbiology, 2017)
The outcome of a host-pathogen interaction is determined by the conditions of the host, the pathogen, and the environment. Although numerous proteomic studies of in vitro-grown microbial pathogens have been performed, in vivo proteomic approaches are still rare. In addition, increasing evidence supports that in vitro studies inadequately reflect in vivo conditions. Choosing the proper host is essential to detect the expression of proteins from the pathogen in vivo. Numerous studies have demonstrated the suitability of zebrafish (Danio rerio) embryos as a model to in vivo studies of Pseudomonas aeruginosa infection. In most zebrafish-pathogen studies, infection is achieved by microinjection of bacteria into the larvae. However, few reports using static immersion of bacterial pathogens have been published. In this study we infected 3 days post-fertilization (DPF) zebrafish larvae with P. aeruginosa PAO1 by immersion and injection and tracked the in vivo immune response by the zebrafish. Additionally, by using non-isotopic (Q-exactive) metaproteomics we simultaneously evaluated the proteomic response of the pathogen (P. aeruginosa PAO1) and the host (zebrafish). We found some zebrafish metabolic pathways, such as hypoxia response via HIF activation pathway, were exclusively enriched in the larvae exposed by static immersion. In contrast, we found that inflammation mediated by chemokine and cytokine signaling pathways was exclusively enriched in the larvae exposed by injection, while the integrin signaling pathway and angiogenesis were solely enriched in the larvae exposed by immersion. We also found important virulence factors from P. aeruginosa that were enriched only after exposure by injection, such as the Type-III secretion system and flagella-associated proteins. On the other hand, P. aeruginosa proteins involved in processes like biofilm formation, and cellular responses to antibiotic and starvation were enriched exclusively after exposure by immersion. We demonstrated the suitability of zebrafish embryos as a model for in vivo host-pathogen based proteomic studies in P. aeruginosa. Our global proteomic profiling identifies novel molecular signatures that give systematic insight into zebrafish-Pseudomonas interaction.